Cognitive performance is associated with worse prognosis in patients with heart failure with reduced ejection fraction. (21st August 2020) - Fino, Patrícia; Sousa, Rita Matos; Carvalho, Renata; Sousa, Nuno; Almeida, Filipa; Pereira, Vítor Hugo
Abstract: Aims: Heart failure (HF) is a complex clinical syndrome with multiple comorbidities. Cognitive impairment, stress, anxiety, depression, and lower quality of life are prevalent in HF. Herein, we explore the interplay between these parameters and study their value to predict major adverse cardiovascular events (MACEs) and health‐related quality of life (HrQoL) in patients with HF with reduced ejection fraction using guideline recommended assessment tools. Methods and results: We conducted a longitudinal study using a sample of 65 patients from two hospitals. A battery of tests was applied to assess cognition [Montreal Cognitive Assessment (MoCA)], stress (Perceived Stress Scale‐10), anxiety, and depression (Hospital Anxiety and Depression Scale) at baseline. MACEs were registered using clinical records. HrQoL was estimated using the Kansas City Cardiomyopathy Questionnaire (KCCQ). A descriptive statistical analysis was conducted, and multiple linear and Cox regression models conducted to determine the predictive value of neurocognitive parameters and HrQoL in MACE. Both MoCA [hazard ratio = 0.906 (0.829–0.990); P = 0.029] and KCCQ scores were predictors of MACE, but not of overall mortality. Anxiety, depression, and stress scores did not predict MACE. However, anxiety ( β = −0.326; P = 0.012) and depression levels ( β = −0.309; P = 0.014) were independent predictors of the KCCQ score. Conclusions: The MoCA score and HrQoL were predictors of MACE‐free survival. Anxiety and depression were good predictors of HrQoL, but not of MACE‐free survival.